2013
DOI: 10.1128/cvi.00305-13
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of Fasciola gigantica Circulating Antigen in Sera of Infected Individuals for Laboratory Diagnosis of Human Fascioliasis

Abstract: c Currently, the laboratory diagnosis of human fascioliasis is based on the parasitological examination of parasite eggs in stool specimens and serological detection of specific antibodies in serum samples, which are often unreliable diagnostic approaches. Ideally, a sensitive and specific diagnostic test for Fasciola infection should be based on the detection of circulating Fasciola antigen, which implies active infection. Here, a 27-kDa-molecular-mass antigen was identified in a Fasciola gigantica adult worm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…In contrast there was correlation in Huacullani regarding low burden cases (<400 epg) (Valero et al 2012 a ). Observed lack of correlation in two of these studies is in contrast to the positive correlation between epg counts and OD readings obtained by other authors (Espino and Finlay, 1994; Mezo et al 2004; Demerdash et al 2011; Attallah et al 2013), but agrees with results found in hospital patients (Ubeira et al 2009). Results suggest that the OD/epg correlation found by other authors may be due to the analysis of stool from low to very low fluke burdens.…”
Section: Diagnosis With Stool Samplessupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast there was correlation in Huacullani regarding low burden cases (<400 epg) (Valero et al 2012 a ). Observed lack of correlation in two of these studies is in contrast to the positive correlation between epg counts and OD readings obtained by other authors (Espino and Finlay, 1994; Mezo et al 2004; Demerdash et al 2011; Attallah et al 2013), but agrees with results found in hospital patients (Ubeira et al 2009). Results suggest that the OD/epg correlation found by other authors may be due to the analysis of stool from low to very low fluke burdens.…”
Section: Diagnosis With Stool Samplessupporting
confidence: 81%
“…Besides the most used ES78 monoclonal antibody used for the FasciDIG test (Espino et al 1993, 1998; Espino and Finlay, 1994; Marcet Sanchez et al . 2012) and MM3 monoclonal antibody used for the MM3-COPRO test (Ubeira et al 2009; Valero et al 2009 b , 2012 a ; Muiño et al 2011), other monoclonal antibodies have also been described (Arafa et al 1999; El-Bassiouny et al 2008; Demerdash et al 2011; Allam et al 2012; Attallah et al 2013). Several are commercially available: (i) ‘ Fasciola hepatica Antigen ELISA Kit Bio K 201’; (ii) ‘Bovine Fasciola hepatica Antigenic ELISA Kit’; (iii) ‘ Fasciola hepatica Ag’; (iv) ‘FasciDIG IPK La Havana’.…”
Section: Diagnosis With Stool Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…. Similar ELISA tests are available for F. gigantica using a variety of different antigens: (a) Fas1 and Fas2 cysteine proteases, resulting in 91·9% and 89·1%, sensitivity and specificity, respectively ; (b) sandwich ELISA using fatty acid binding protein, resulting in 94·7% sensitivity and 84·62% specificities ; (c) 27 kDa circulating antigen from sera of infected individuals gave >93% sensitivity and specificity . A lateral flow test (SeroFluke) was developed by Martinez‐Sernandez and colleagues using samples obtained from F. hepatica‐ infected patients in Spain and Portugal, for use with serum or whole blood samples, which requires minimal training .…”
Section: Diagnosis Of Human Liver Fluke Infectionmentioning
confidence: 99%
“…Fascioliasis is a food-borne zoonotic disease caused by liver trematodes of the genus Fasciola . The disease has been considered as a global disease of domestic ruminants and cause economic losses in livestock [ 1 ]. Nowadays, human fascioliasis has been recognized as an important reemerging parasitic disease by World Health Organization, with an estimated 17 million people affected worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%